A detailed review on CO2 two-phase ejector flow modeling. (1st December 2020) - Ringstad, Knut Emil; Allouche, Yosr; Gullo, Paride; Ervik, Åsmund; Banasiak, Krzysztof; Hafner, Armin
Highlights: Studies on CO 2 two-phase ejector models are exhaustively reviewed. Recent advances in modeling non-equilibrium conditions are included. Available models can reasonably predict super critical motive flow. Current models do not accurately capture suction flow entrainment. Current models need more local experimental data for validation. Abstract: Ejector-equipped vapor-compression systems for refrigeration and cooling, relying solely on CO 2 (R744) as a natural working fluid, are perceived to be an eco-friendly and highly efficient solution for many applications. However, the complexity of two-phase ejector flows makes it very challenging to find realiable and efficient ejector designs. Improved design methods are necessary in order to achieve higher performance in R744 units compared to the traditional compressor-based systems with refrigerants that put a high strain on the environment. Consequently, the development of advanced models and tools for an accurate design of the R744 ejectors has been a highly prioritized research topic. To the best of the authors' knowledge, the current status of R744 ejector models and their limitations has not been thoroughly evaluated yet. To summarise the current state of the art and knowledge gaps, this work presents an exhaustive overview of the available numerical models applied to R744 two-phase ejectors, i.e. multiphase flow modeling, turbulence aspects, numerical solution methods, applications of models, to further encourage the adoption of R744 vapor-compression solutions. Finally, a thorough discussion of different focus points for future research as well as the main challenges in the field is presented.